Liver Abscess due to Enterohepatic Migration of Fish Bone (TAJ: Journal of Teachers Association, 2020)
Liver abscess due to accidentally ingested fish bone is extremely rare; only 30 cases have been described in the literature. We are reporting a 46-year-old female presenting with liver abscess due to enterohepatic migration of accidentally ingested fish bone.TAJ 2020; 33(1): 48-50